Accountability of international territorial administrations : a public law approach - Momirov, Aleksandar; Shaffer, William R., 1942-; Sunde, Jørn Øyrehagen, 1972-; Waltenburg, Eric N., 1965- (Eleven International Publishing ; Sold and distributed in USA and Canada, International Specialized Book Services, 2011)
Click here to read an interview with Gunnar Grendstad andJrn yrehagen Sunde about the book inJuristen; a Norwegian journal. Norway's Supreme Court is one of the most powerful Supreme Courts in Europe. Thisposition is in large parts due to the role and expansion of the law clerks on the Court. Beginning in 1957 with a single clerk, the number of law clerks has increased dramatically. Today, the clerks outnumber the justices, andtheir tasks have expanded considerably. In 1957 the task was to prepare civil appeals. Today,clerks assist in most stages of the Court's decisional process, including the writing of the final decision. Theexpansion and institutionalisation of the clerk unit have enabled the justices to commence on policymaking and on developing the law. The law clerks have been key in the development of a more proactive and powerful Norwegian Supreme Court. Thisbookis the first comprehensive study of law clerks in a European Supreme Court. It will be valuable to lawyers, historians and political scientists who care about the expanding role of courts and the impact of courts on politics, society, and the legal system.